PENERAPAN MEDIA EDUKATIF TEKA-TEKI SILANG MATERI MEMBACA DONGENG UNTUK MENINGKATKAN HASIL BELAJAR PADA SISWA KELAS III SDN DUKUH KUPANG V SURABAYA - Sheren Priscilia Shabilla; Suprihatien; Leni Yuliana (Pusat Riset dan Inovasi Nasional, 2023)
This study was prepared with the aim of improving student learning outcomes by using learning media tools that are games, namely educational media crossword puzzles in fairy tale reading learning material for third grade students of SDN Dukuh Kupang V, Surabaya. The improvement of student learning outcomes referred to in this study, namely student learning by using crossword puzzle educational media that can produce an increase in the final learning outcomes. This type of research is quantitative research, where the teacher is the implementer of learning while the researcher is the observer. This research design uses an experimental model. The object of research is student learning outcomes. Data collection techniques used questionnaires, observations, and tests. The variables in this study used independent variables in the form of learning media and the dependent variable was learning outcomes. The class in this study was divided into two, namely the control class and the experimental class, each of which received treatment in different studies so that the two classes experienced an increase or decrease in their results. The experimental class experienced an increase in learning outcomes of 84% (very good category), then the control class decreased to -80% (very poor category). Thus the use of crossword puzzle educational learning media in Indonesian language subjects can improve student learning outcomes )of class III students at SDN Dukuh Kupang V, Surabaya.